Post-disaster psychosocial services across Europe: the TENTS project - Witteveen, Anke B.; Bisson, Jonathan I.; Ajduković, Dean; Arnberg, Filip K.; Bergh Johannesson, Kerstin; Bolding, Hendrieke B.; Elklit, Ask; Jehel, Louis; Johansen, Venke A.; Lis-Turlejska, Maja; Nordanger, Dag; Orengo-García, Francisco; et al. (2012)
At present post-disaster activities and plans seem to vary widely. An adequate estimation of the availability of post-disaster psychosocial services across Europe is needed in order to compare them with recently developed evidence-informed psychosocial care guidelines. Here we report on the results of a cross-sectional web-based survey completed in 2008 by two hundred and eighty-six representatives of organizations involved in psychosocial responses to trauma and disaster from thirty-three different countries across Europe. The survey addressed planning and delivery of psychosocial care after disaster, methods of screening and diagnosis, types of interventions used, and other aspects of psychosocial care after trauma. The findings showed that planning and delivery of psychosocial care was inconsistent across Europe. Countries in East Europe seemed to have less central coordination of the post-disaster psychosocial response and fewer post-disaster guidelines that were integrated into specific disaster or contingency plans. Several forms of psychological debriefing, for which there is no evidence of efficacy to date, were still used in several areas particularly in North Europe. East European countries delivered evidence-based interventions for PTSD less frequently, whilst in South- and South-Eastern European countries anxiety suppressing medication such as benzodiazepines were prescribed more frequently to disaster victims than in other areas. Countries across Europe are currently providing sub-optimal psychosocial care for disaster victims. This short report shows that there is an urgent need for some countries to abandon non-effective interventions and others to develop more evidence based and effective services to facilitate the care of those involved in future disasters.
Projekt MZOS
ENG